Prospective Study of the Emfit Movement Monitor. (November 2013) - Poppel, Kate Van; Fulton, Stephen P.; McGregor, Amy; Ellis, Michelle; Patters, Andrea; Wheless, James
Sudden unexplained death in epilepsy (SUDEP) is associated with generalized tonic-clonic seizures and occurs most often when patients are in bed. There are several seizure detection monitors on the market, but little data are available on the sensitivity and specificity of these devices. We recently tested 2 models of seizure detection alarms with disappointing results. Here we tested the Emfit movement monitor on children with various seizure types who also had standard video electroencephalography (EEG), cardiopulmonary, and nursing monitoring. Video EEG records were reviewed to detect any seizures. In 45 patients, 78 seizures were recorded by video EEG. The Emfit movement monitor captured 23 seizure events (30%) in total, and 15 of the 28 (54%) that occurred during sleep. Most importantly, the alarm was activated with 11 of the 13 (85%) generalized tonic-clonic seizures that occurred in sleeping children. The Emfit movement monitor performed very well in comparison to previously tested devices.